Revolutionizing consumer loans: the role of emerging technologies in shaping credit products for Non-Bank Financial Institutions (NBFI) - Chakroborty, Sudip (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.